Definição de um Sistema de Projeção Cartográfica para Mapeamento Urbano no Estado do Rio Grande do Sul - DA ROCHA, RONALDO DOS SANTOS (Pesquisas em Geociências, 1996)
This work studies the use of map projections in large scale mapping to provide support for a Land Information System. For this purpose, evaluations of the map projections commonly used in France, Switzerland, USA and Brazil are presented. The adequate precision to record property lines in a cadastral survey is identified and then compared to the linear distortions inherent to the map projections used in Brazil. Based upon these discrepancies, an optimum projection was developed to be used in large scale cartography in the State of Rio Grande do SuI. The expressions to transform geographic coordinates into projection coordinates are also presented. Several tests have been performed and the results are portrayed on a comparative chart showing the values of geodectics, plane distance on the UTM projection and plane distance on the above mentioned projection. The identified projection presents linear distortions lower than the established precision for property delimitation, corroborating the validity of its use in a Land Information System.